PENGARUH MEDIA SOSIAL DAN KOMUNIKASI ANTARBUDAYA TERHADAP TRANSFORMASI BUDAYA BADUY LUAR - Arya Aditya Natayuda; Hanindyalaila Pienrasmi (ADISAM PUBLISHER, 2026)
This study examines the influence of social media and intercultural communication on cultural transformation within the Outer Baduy community. The research departs from concerns regarding the tension between technological modernization and the preservation of indigenous cultural identity. Using a quantitative survey approach, data were collected from 390 respondents through structured questionnaires. Social media and intercultural communication were treated as independent variables, while cultural transformation served as the dependent variable. Data were analyzed using validity and reliability testing, classical assumption tests, multiple linear regression, t-tests, and F-tests. The findings indicate that social media significantly affects cultural transformation (t = 7.374; p < 0.05), while intercultural communication also has a significant effect (t = 6.640; p < 0.05). Simultaneously, both variables show significant influence on cultural transformation (F = 12.743; p < 0.05). The study reveals that technological openness and intercultural interaction contribute to shifts in identity, values, and social behavior among the Outer Baduy community. However, these transformations tend to occur through adaptive cultural negotiation rather than through erosion of traditional identity. This research contributes to communication studies by demonstrating that digital media can function not only as a driver of modernization but also as a medium for cultural adaptation.